Psikologi Manajemen dalam Pendidikan Tinjauan Literatur Sistematis Peningkatan Kinerja Pendidik dan Efektivitas Pembelajaran - Abu Muhlis; Diana Dwi Septyaningrum; Ramadani Ramadani; Mu’alimin Mu’alimin (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
Management psychology is a crucial aspect in enhancing learning effectiveness and improving the performance of educational institutions in the face of contemporary educational challenges. This approach emphasizes the role of psychological factors such as motivation, leadership, communication, and organizational culture in supporting effective educational management. This study aims to examine the role of management psychology in improving educational quality and to explore how psychological aspects contribute to organizational effectiveness. The research uses a literature review method, drawing data from Google Scholar and Publish or Perish (PoP) with publications from 2020 to 2026 using the keyword “management psychology.” From 21 initial articles, 15 met the screening criteria, and five main articles were analyzed in depth. The findings highlight three key themes: improving performance and learning outcomes, strengthening leadership and organizational communication, and managing conflict and human resources. Overall, the literature shows that psychological approaches significantly enhance the effectiveness of educational organizations. In conclusion, management psychology plays a strategic role in educational management, and future research should expand the scope of literature and integrate quantitative methods to strengthen empirical findings.